2019
DOI: 10.1111/dom.13658
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in patients with type 2 diabetes receiving once‐weekly dulaglutide plus insulin lispro or insulin glargine plus insulin lispro: A post‐hoc analysis of the AWARD‐4 study across baseline body mass index subgroups

Abstract: Aims: Insulin-treated patients with type 2 diabetes (T2D) and obesity are challenged in achieving body weight stability or reduction, in addition to glycaemic control. Post-hoc analyses of body weight and insulin dose data from the AWARD-4 trial involved comparison of treatment with once-weekly dulaglutide 1.5 mg (N = 295) or 0.75 mg (N = 293) and treatment with daily insulin glargine (N = 296), each with prandial insulin lispro (± metformin).Materials and methods: Changes in weight and in the proportion of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In these analyses, greater weight loss was observed with increasing baseline BMI for both semaglutide and dulaglutide, aligning with what has been previously reported for semaglutide 23 and dulaglutide. 35 While percentage weight loss was also greater with semaglutide versus dulaglutide, the percentage change in weight loss was generally of a similar magnitude across BMI categories, indicating that the weight-loss pattern observed across the HbA 1c subgroup categories may be associated with subjects' baseline BMI. High BMI is associated with an insulin-resistant phenotype in some patients, 3 and less weight loss is observed in patients with diabetes who are insulin resistant than in those with insulin sensitivity.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In these analyses, greater weight loss was observed with increasing baseline BMI for both semaglutide and dulaglutide, aligning with what has been previously reported for semaglutide 23 and dulaglutide. 35 While percentage weight loss was also greater with semaglutide versus dulaglutide, the percentage change in weight loss was generally of a similar magnitude across BMI categories, indicating that the weight-loss pattern observed across the HbA 1c subgroup categories may be associated with subjects' baseline BMI. High BMI is associated with an insulin-resistant phenotype in some patients, 3 and less weight loss is observed in patients with diabetes who are insulin resistant than in those with insulin sensitivity.…”
Section: Discussionmentioning
confidence: 88%
“…21 22 Post hoc analyses of the SUSTAIN and the AWARD trials have analysed patient subgroups across the continuum of T2D care. [23][24][25][26][27][28][29][30][31][32][33][34][35] Such analyses showed consistent, clinically relevant reductions in glycated haemoglobin (HbA 1c ) and body weight (BW) with semaglutide across patient subgroups based on characteristics including age, baseline body mass index (BMI), baseline HbA 1c , diabetes duration, race and ethnicity. 23-26 28 Dulaglutide has also been shown to be efficacious across subgroups based on sex, age, duration of diabetes, beta-cell function, HbA 1c , BW and BMI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A chronic inflammatory state linked to obesity leads to dysregulation of the endocrine and paracrine actions of adipocyte-derived factors, which disrupt vascular homeostasis and contribute to endothelial vasodilator dysfunction by determining, among other effects, an imbalance in the endothelin-1/nitric oxide pathway [46]. Considering these premises, the reduction of body weight and BMI observed in the dulaglutide arm at the nine-month follow-up might lead to a reduction in the systemic inflammatory state, the resumption of the correct mechanisms of vascular homeostasis and, as observed in our trial, an improvement in the vascular health indexes.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study (47) demonstrated that the reduction of FPG and improvement in glycaemic variability are correlated with the reduction of oxidative stress on the vascular endothelium.…”
Section: Discussionmentioning
confidence: 93%